Consequence Of Dividend-Payout On Performance Evaluation Of Top It Companies In India - M S, KOKILA; ZIPPORAH, G.; A K, SRUJANA (The journal of contemporary issues in business and government, 2021)
In the current business environment dividend payout is very important matter and especially in evaluating the performance of the firms. Dividend is defined as a part of the profits which is paid to the share-holders reciprocally for investing their money within the organization. The key element in firm, when it comes to performance evaluation is selecting successfully and using the dividend policy appropriately. The main aim for investigating this paper is to know the consequence of dividend payout in the performance-evaluation of the top IT companies- India from the past 10 years of time i.e., from 2012-2021. Four variables named: 1. Dividend Payout Ratio (DPR), 2. Return on Capital Employed (ROCE), 3. Return on Equity (ROE), and 4. Return on Assets (ROA). All 4 of this is used by researchers to carry out the analysis. Here in this research work Performance evaluation is considered as dependent variable by Return on Capital Employed (ROCE), Return on Equity (ROE), and Return on Assets (ROA) and Dividend Payout Ratio (DPR) as independent variable. Secondary data of the variables are gathered from balance-sheet and the statements of income of the top 5 IT companies taken for the study. The secondary data collected for this research work is analyzed and appropriate statistical tools like ANOVA single factor, and correlation technique and descriptive statistics is used. The researcher’s results states that the DPR is related with all variables dependent i.e., ROCE, ROA and ROE, which is used in the study.